2008
DOI: 10.1177/104063870802000317
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinating Activity of Serovar Reference Strains of Ornithobacterium Rhinotracheale

Abstract: Abstract. In the present study, the hemagglutinating activity of 9 reference strains (serovars A-I) of Ornithobacterium rhinotracheale was investigated by using fresh erythrocytes from 15 different species: chicken (broiler, rooster, hen), turkey, pigeon, quail, duck, Harris hawk (Parabuteo unicinctus), house finch (Carpodacus mexicanus), cow, sheep, horse, dog, rabbit, pig, human (groups A, B, AB, and O), and rainbow trout (Oncorhynchus mykiss). All 9 strains agglutinated rabbit erythrocytes. None of the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The hemagglutinating activity of all stable O. rhinotracheale SCVs and WT isolates was tested with fresh chicken, pigeon, and rabbit erythrocytes, as described previously (15,34). Briefly, fresh bacterial suspensions of the O. rhinotracheale isolates were prepared from 48-h cultures on SBA; they were harvested in 1.5 ml of PBS (pH 7.0), adjusted to an OD 600 value of 1.5, and washed 3 times with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The hemagglutinating activity of all stable O. rhinotracheale SCVs and WT isolates was tested with fresh chicken, pigeon, and rabbit erythrocytes, as described previously (15,34). Briefly, fresh bacterial suspensions of the O. rhinotracheale isolates were prepared from 48-h cultures on SBA; they were harvested in 1.5 ml of PBS (pH 7.0), adjusted to an OD 600 value of 1.5, and washed 3 times with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…There are 18 serotypes for ORT, with the majority of chicken isolates belonging to four serotypes A, B, D and E (Chansiripornchai et al 2007;Thachil et al 2007). Haemagglutinating activity of ORT serovars has been studied by using fresh erythrocytes from different species (Vega et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Five ORT reference strains were used, corresponding to serovars A, B, C, D, and E (Table 1). All the strains were cultured on 5% ovine blood agar (DIBICO, Mexico City, Mexico) and further incubated at 37°C in 5% CO 2 for 48 h (Soriano et al, 2003, Vega et al, 2008. S. mutans ATCC 25125 was used as a positive control of biofilm-producing bacteria, and was cultured in the same medium and under the same culture conditions as ORT (Yoshida & Kuramitsu, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…This bacterium is able to adhere to tracheal cells in chickens and possesses a haemagglutinin and a neuraminidase (Soriano et al, 2003;Vega et al, 2008;De Haro-Cruz et al, 2013;Kastelic et al, 2013); additionally, it has been reported that some ORT isolates are able to produce a biofilm (Vichi et al, 2012). A biofilm is considered to be a complex microbial community where microorganisms synthesize an exopolysaccharide matrix that protects the microorganisms against the environment, antimicrobial agents and the immune response of the host, it can adhere to either an inert surface or a live tissue (Lasa et al, 2005;Vila et al, 2008;Castrillón et al, 2010).…”
Section: Introductionmentioning
confidence: 99%